2018
DOI: 10.1126/science.aat3872
|View full text |Cite
|
Sign up to set email alerts
|

Directional control of a processive molecular hopper

Abstract: Intrigued by the potential of nanoscale machines, scientists have long attempted to control molecular motion. We monitored the individual 0.7-nanometer steps of a single molecular hopper as it moved in an electric field along a track in a nanopore controlled by a chemical ratchet. The hopper demonstrated characteristics desired in a moving molecule: defined start and end points, processivity, no chemical fuel requirement, directional motion, and external control. The hopper was readily functionalized to carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 51 publications
5
92
0
3
Order By: Relevance
“…Interestingly, the electrostatic force from the ΔΨ can be sufficiently strong to break a disulfide bond, permitting a subsequent large conformational change in the MP, as shown experimentally in the VGIC . Recently, an artificially designed, ΔΨ‐driven molecular motor running inside a membrane‐embedded channel was reported to operate using a similar, disulfide‐bond hopping mechanism …”
Section: Two‐state Rigid‐body Motion Is a Common Way To Utilize Electmentioning
confidence: 90%
“…Interestingly, the electrostatic force from the ΔΨ can be sufficiently strong to break a disulfide bond, permitting a subsequent large conformational change in the MP, as shown experimentally in the VGIC . Recently, an artificially designed, ΔΨ‐driven molecular motor running inside a membrane‐embedded channel was reported to operate using a similar, disulfide‐bond hopping mechanism …”
Section: Two‐state Rigid‐body Motion Is a Common Way To Utilize Electmentioning
confidence: 90%
“…The mechanism of plasmon‐induced chemical reaction, a key route in photocatalysis, remained controversial over years due to the difficulty in directly observing such a process. In a recent study, STM was applied to realize for the first time the real‐space and real‐time monitoring of plasmon‐induced chemical reaction at a single molecule level . Through the comparison of the spatial distribution of isolated dimethyl disulfide (CH 3 S) 2 molecule on Ag or Cu surfaces before and after localized surface plasmon excitation, Figure , it was found that those (CH 3 S) 2 near the tip position could indeed split into two identical ball shaped protrusions, although the majority remained as elliptical.…”
Section: Manipulation Of Single Molecule Reactionmentioning
confidence: 99%
“…The time required for the plasmon‐induced dissociation ( t R ) is directly read from the current trace . Reproduced with permission . Copyright 2018, AAAS.…”
Section: Manipulation Of Single Molecule Reactionmentioning
confidence: 99%
“…Communications Figure 2. Excerpts of 400 MHz 1 HNMR spectra (323 Ki nCDCl 3 )showing the amide resonances of 2 at 1mm (a) and in the presence of 3equiv of 5 after:b)5min;c)60min. and d) at equilibrium.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1] Miniature artificial walkers have also been described. [2,3] Tr anslation directionality can be imposed when changing the preferred position of macrocycles on am olecular rod by means of an external stimulus.B iased Brownian motion then allows the system to relax to its new preferred state leading to anet flux from one station to the other. [4] Reverting the preferred position back to its original state leads to ar eversal of translation and shuttling is observed.…”
mentioning
confidence: 99%